New phenylaniline derivatives as modulators of amyloid protein precursor metabolism. Issue 8 (1st May 2018) - Gay, Marion; Carato, Pascal; Coevoet, Mathilde; Renault, Nicolas; Larchanché, Paul-Emmanuel; Barczyk, Amélie; Yous, Saïd; Buée, Luc; Sergeant, Nicolas; Melnyk, Patricia
Graphical abstract: Highlights: Synthesis of modulators of amyloid protein precursor metabolism starting from chloroquine and amodiaquine backbones. The reduction of Aβ levels including Aβ40 and Aβ42 were quantified. The metabolism of APP is analysed and the accumulation of CTFα and AICD were determined. Compounds with the best efficiency had no cellular toxicity at concentration lower than 100 µM. Abstract: The chloroquinoline scaffold is characteristic of anti-malarial drugs such as chloroquine (CQ) or amodiaquine (AQ). These drugs are also described for their potential effectiveness against prion disease, HCV, EBV, Ebola virus, cancer, Parkinson or Alzheimer diseases. Amyloid precursor protein (APP) metabolism is deregulated in Alzheimer's disease. Indeed, CQ modifies amyloid precursor protein (APP) metabolism by precluding the release of amyloid-beta peptides (Aβ), which accumulate in the brain of Alzheimer patients to form the so-called amyloid plaques. We showed that AQ and analogs have similar effects although having a higher cytotoxicity. Herein, two new series of compounds were synthesized by replacing 7-chloroquinolin-4-amine moiety of AQ by 2-aminomethylaniline and 2-aminomethylphenyle moieties. Their structure activity relationship was based on their ability to modulate APP metabolism, Aβ release, and their cytotoxicity similarly to CQ. Two compounds 15a, 16a showed interesting and potent effect on the redirection of APP metabolism toward a decrease of Aβ peptide release (in the same range compared to AQ), and a 3–10-fold increased stability of APP carboxy terminal fragments (CTFα and AICD) without obvious cellular toxicity at 100 µM.